2023
DOI: 10.1017/jlc.2023.18
|View full text |Cite
|
Sign up to set email alerts
|

Lower Court Influence on High Courts: Evidence from the Supreme Court of the United Kingdom

Jennifer Bowie,
Ali S. Masood,
Elisha C. Savchak
et al.

Abstract: Do lower court judges influence the content of Supreme Court opinions in the United Kingdom? Leveraging original data, we analyze opinion language adoption practices of the UK Supreme Court. We advance a theory where the justices’ choices to adopt language from lower court opinions are influenced by Supreme Court-level attributes and Court of Appeal case characteristics. We uncover compelling evidence that UK Supreme Court justices incorporate language extensively from the written opinions of the Court of Appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…The author suggests that this relatively static patent length is due to an informal incentive structure that encourages patent prosecutors to draft claims that follow a highly standardized format. Finally, Bowie et al (2023) used opinion lengths to study British lower courts' influence on the British Supreme Court. The authors found that the length of a lower court's opinion was positively correlated with influence, as measured by the extent to which the British Supreme Court borrowed language from the lower court's opinions.…”
Section: Law-as-datamentioning
confidence: 99%
“…The author suggests that this relatively static patent length is due to an informal incentive structure that encourages patent prosecutors to draft claims that follow a highly standardized format. Finally, Bowie et al (2023) used opinion lengths to study British lower courts' influence on the British Supreme Court. The authors found that the length of a lower court's opinion was positively correlated with influence, as measured by the extent to which the British Supreme Court borrowed language from the lower court's opinions.…”
Section: Law-as-datamentioning
confidence: 99%